2014
DOI: 10.1111/pcn.12245
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal non‐epileptic events in infants and toddlers: A phenomenologic analysis

Abstract: Aim:The aim of this study was to analyze in detail the clinical phenomenology of paroxysmal nonepileptic events (PNEE) in infants and toddlers. Methods:We studied all children aged ≤2 years who were diagnosed with PNEE based on videoelectroencephalographic (VEEG) recordings. We analyzed the following four clinical domains of each clinical event: (i) motor manifestations (body/limb jerking, complex motor, and asymmetric limb posturing); (ii) oral/vocal (crying, vocalization, sighing); (iii) behavioral change (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 22 publications
3
33
0
1
Order By: Relevance
“…Physiological nonepileptic events differ from psychogenic nonepileptic seizures in many aspects including the age of symptom onset. Chen et al [5] noted that physiologic disorders including staring, sleep myoclonus, shuddering, and behavioral events comprise the majority of PNEs in infants and toddlers. On the other hand, Luat et al [6] found that psychogenic nonepileptic seizures tend to occur more frequently in school-age children and adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…Physiological nonepileptic events differ from psychogenic nonepileptic seizures in many aspects including the age of symptom onset. Chen et al [5] noted that physiologic disorders including staring, sleep myoclonus, shuddering, and behavioral events comprise the majority of PNEs in infants and toddlers. On the other hand, Luat et al [6] found that psychogenic nonepileptic seizures tend to occur more frequently in school-age children and adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…The breath-holding spells were classified as mild, moderate, and severe (Table 1). Patients were excluded from the study with spells associated with metabolic problems, electrolyte disturbances, and trauma to avoid including children with seizures that can mimic breath-holding spells 17,18. In addition, a total of 12 patients were excluded from the study due to hypocalcemia-related tremor (2), early childhood benign myoclonus (4), hyperekplexia (2), benign infantile epilepsy (3), and benign paroxysmal vertigo (1).…”
Section: Methodsmentioning
confidence: 99%
“…According to Visser et al [3], the incidence of paroxysmal disorders in infancy is 8.9%, of which 52% are physiological events. tion, and alleviating parents' worries [2,[5][6][7]. Diagnosis can usually be made based on detailed history and examination, with the knowledge of several types of NPEs with distinctive clinical presentations [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…tion, and alleviating parents' worries [2,[5][6][7]. Diagnosis can usually be made based on detailed history and examination, with the knowledge of several types of NPEs with distinctive clinical presentations [5,7]. However, differentiation between true seizures and NPEs is difficult during infancy due to variations in semiology and incorrect history provided by parents or caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation